2022
DOI: 10.5194/gmd-15-1355-2022
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the interactions between ice sheets, sea level and the solid Earth on a range of timescales: a new “time window” algorithm

Abstract: Abstract. Retreat and advance of ice sheets perturb the gravitational field, solid surface and rotation of the Earth, leading to spatially variable sea-level changes over a range of timescales O(100−6 years), which in turn feed back onto ice-sheet dynamics. Coupled ice-sheet–sea-level models have been developed to capture the interactive processes between ice sheets, sea level and the solid Earth, but it is computationally challenging to capture short-term interactions O(100−2 years) precisely within longer O(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Since the change in GIA signal increases due to fast unloading in a warming climate, smaller time steps of 1000 and 500 years were chosen during the deglaciation. Han et al (2022) showed that coupling time steps of 400 years are optimal for the deglaciation phase using a coupled 1D GIAice-sheet model, but their method assumes a constant topography during one coupling timestep which requires smaller timesteps than the coupling method presented in this study.…”
Section: Size Of the Coupling Time Stepmentioning
confidence: 91%
“…Since the change in GIA signal increases due to fast unloading in a warming climate, smaller time steps of 1000 and 500 years were chosen during the deglaciation. Han et al (2022) showed that coupling time steps of 400 years are optimal for the deglaciation phase using a coupled 1D GIAice-sheet model, but their method assumes a constant topography during one coupling timestep which requires smaller timesteps than the coupling method presented in this study.…”
Section: Size Of the Coupling Time Stepmentioning
confidence: 91%
“…The sea level code used to generate this data is published in association with Han et al. (2022). Natural Earth country polygons and Pacific boundaries data are available at http://www.naturalearthdata.com.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…To explore possible AIS-sourced SLR impacts at AOSIS locations, we provide new SLR fingerprints under two emissions scenarios spanning three centuries (see Data Availability Statement). Sea level fingerprints associated with a recent projection of the AIS from DeConto et al ( 2021) are generated using a gravitationally self-consistent sea level model that includes viscoelastic deformation, Earth rotational effects and migrating shorelines (Gomez et al, 2010;Han et al, 2022). Sea level predictions are normalized by the global mean sea level equivalent change calculated as in Gomez et al (2010) by distributing meltwater evenly over modern global topography (NOAA, 2009), and allowing for water to inundate areas freed of marine ice.…”
Section: Projections Of Ais Slr For Aosis Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-D GIA models such as Latychev et al, 2005, or van der Wal et al, 2015 and be of sufficient spatiotemporal resolution to capture the geometry of grounded ice cover (e.g. Han et al, 2022). Commonly, GIA, ice-sheet and coupled ice-sheet-GIA modelling (e.g.…”
Section: Introductionmentioning
confidence: 99%